IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY PT KAI DAOP 8 SURABAYA DALAM PROGRAM RAIL CLINIC - Sulistyo Rahayu Ningrum; Fitria Widiyani Roosinda (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2020)
This research is the flagship Program of the Corporate Social Responsibility (CSR) Rail Clinic at DAOP 8 Surabaya, as a form of public welfare efforts. PT Kereta Api Indonesia (Persero) DAOP 8 Surabaya conducts the healthcare train service through the Rail Clinic program. The type of research used is descriptive with a qualitative approach. The subject of this study consists of the Staff PR PT KAI DAOP 8 Surabaya and its people. Data collection techniques are performed using in-depth interviews and observations. Analysis of the data done by gaining an understanding of the writing focus will then be drawn a conclusion of a general understanding based on reality. The results of this research shows the flagship Program of PT KAI DAOP 8 Surabaya, the Rail Clinic there are six points in the main activity of Corporate Social Responsibility (CSR) including cause promotion, cause related marketing, corporate social marketing, corporate philanthropy, community valunteering and Socialy responsible bussines practice. Keywords: Corporate Social Responsibility (CSR), Rail Clinic Program.